The ConWip production control system: a systematic review and classification. Issue 17 (2nd September 2018) - Jaegler, Yann; Jaegler, Anicia; Burlat, Patrick; Lamouri, Samir; Trentesaux, Damien
Abstract : In the past decade, a growing body of literature has investigated the CONstant Work In Progress (ConWip) production control system (PCS). In view of the current industrial challenges entailing adaptability, product customisation, decreasing leadtimes and customer satisfaction, ConWip seems to be an effective and adaptive PCS for manufacturers. This paper aims to update the last ConWip systematic review that dates back to 2003 and to provide a guide for understanding through an original classification method. This method enables the differentiation of papers that concentrate on ConWip sizing, performance and context as well as a comparison with other PCSs. In addition to providing a key to interpreting the research approaches, the criteria considered answers questions on how to implement, how to optimise and why and when to use ConWip. Finally, the most relevant research avenues are highlighted to provide future lines of research.